2022
DOI: 10.3390/genes13112018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miRNA Profile in High Risk of Preterm Birth during Early and Mid-Pregnancy

Abstract: In recent years evidence has been accumulated showing that miRNAs can act as potential biomarkers or targets for therapy of preterm birth, one of the most important problems in modern obstetrics. We have performed a prospective study of the miRNA profile in the plasma during the first and second trimesters in pregnant women with high risk of preterm birth (n = 13 cases and n = 11 controls). For the study group plasma blood samples at 9–13 weeks before diagnosis and at 22–24 weeks after start of therapy were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Illarionov et al conducted a prospective study on miRNA profiles in plasma during the first trimester, revealing discernible differences in levels among women at high risk of preterm birth. The study identified 15 dysregulated miRNAs, highlighting the potential utility of early miRNA profiles in predicting the risk of preterm birth [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illarionov et al conducted a prospective study on miRNA profiles in plasma during the first trimester, revealing discernible differences in levels among women at high risk of preterm birth. The study identified 15 dysregulated miRNAs, highlighting the potential utility of early miRNA profiles in predicting the risk of preterm birth [29].…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of miRNAs demonstrate dynamic fluctuations across the different trimesters of pregnancy, with specific miRNAs upregulated in the first trimester and others not showing differential expression until later stages [29]. This highlights the complex regulation of miRNA expression throughout pregnancy and its potential impact on preterm labor.…”
Section: Positive Correlationmentioning
confidence: 98%
“…When focusing these analyses on miRNAs with the highest read counts (i.e., baseMean > 1000), we identified three upregulated (i.e., miR-151-3p, miR-199a-5p and miR-340) and three down regulated (i.e., miR-122, miR-378 and miR-486) miRNAs. Although we are the first, to our knowledge, to determine that the deregulation of these EV-miRNAs may be associated with percreta pregnancies, recent studies have shown that the deregulated expression of miR-NAs (i.e., as EV-miRNAs and circulating miRNAs) is also associated with other adverse pregnancy outcomes [71,72], including preeclampsia and spontaneous pre-term birth [73][74][75][76]. For example, miR-486, which we found to be downregulated in placental EVs of placenta percreta pregnancies, has been found to be upregulated in EVs derived from human placental microvascular endothelial cells, and it is associated with the regulation of proliferation, migration, and invasion of trophoblast cells, thus contributing to poor placentation and the clinical manifestation of preeclampsia [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Illarionov et al carried out a prospective study of miRNAs in plasma during the first and second trimesters in pregnant women at high risk of PTB (13 cases and 11 controls) [107]. Plasma blood samples at 9-13 WG and 22-24 WG were available for the study group.…”
Section: Expression Of Mirnas In Biofluids and Ptbmentioning
confidence: 99%